The accuracy of restoration of femoral head centre of rotation in the anteroposterior plane after uncemented total hip arthroplasty: a CT-based study. Issue 3 (1st March 2022) - Rajpura, Asim; Asle, Soheil Ghane; Ait Si Selmi, Tarik; Board, Tim
Abstract : Aims: Hip arthroplasty aims to accurately recreate joint biomechanics. Considerable attention has been paid to vertical and horizontal offset, but femoral head centre in the anteroposterior (AP) plane has received little attention. This study investigates the accuracy of restoration of joint centre of rotation in the AP plane. Methods: Postoperative CT scans of 40 patients who underwent unilateral uncemented total hip arthroplasty were analyzed. Anteroposterior offset (APO) and femoral anteversion were measured on both the operated and non-operated sides. Sagittal tilt of the femoral stem was also measured. APO measured on axial slices was defined as the perpendicular distance between a line drawn from the anterior most point of the proximal femur (anterior reference line) to the centre of the femoral head. The anterior reference line was made parallel to the posterior condylar axis of the knee to correct for rotation. Results: Overall, 26/40 hips had a centre of rotation displaced posteriorly compared to the contralateral hip, increasing to 33/40 once corrected for sagittal tilt, with a mean posterior displacement of 7 mm. Linear regression analysis indicated that stem anteversion needed to be increased by 10.8° to recreate the head centre in the AP plane. Merely matching the native version would result in a 12 mm posterior displacement. Conclusion: This study demonstrates the significant incidence of posterior displacement of the head centre in uncemented hip arthroplasty. Effects of such displacement include a reduction in impingement free range of motion, potential alterations in muscle force vectors and lever arms, and impaired proprioception due to muscle fibre reorientation. Cite this article: Bone Joint Res  2022;11(3):180–188.